Interprofessionality in Health Care - de Souza, Alesandra Perazzoli; dos Santos, Paola Ribas Gonçalves; Cachoeira, Flávia Eduarda; Beal, Solange de Bortoli (Seven Editora, 2023)
Introduction: Interprofessional education in health has been revealed as an important strategy of professional training, in which professionals are able to develop teamwork that seeks to achieve integrality in health care. Objective: Tounderstand interprofessional education in health from the perspective of health education. Method: A bibliographic review with a reflective approach was carried out published between 2011 and 2021 in the SciElo, Pubmed and CAPS databases, using specific descriptors, in Portuguese and English languages, in February 2022. The titles and abstracts were analyzed, followed by the selection of articles that related to the theme, and 7 articles were included in the final sample. Subsequently, the reflection on the theme was carried out. Results and Discussions: From the selection of the articles, it was possible to understand that there is a long trajectory in the implementation of changes in teaching in the context of health education, and there is a need to improve the teaching-service-community integration, as well as to prioritize interdisciplinarity and interprofessionality, enabling cooperation for the exercise of transformative practices. Final considerations: this study revealed the urgent need for the implementation, strengthening and support of interinstitutional partnerships, the promotion of public policies that qualify the faculty for the development of interprofessional education and the strengthening of relations between the university, health institutions and the community. In addition, it pointed out the need to promote a culture of collaboration and teamwork among health professionals, valuing the diversity of knowledge and skills in order to achieve more comprehensive results to improve the results and quality of health care. DOI:https://doi.org/10.56238/globalhealthprespesc-037